Immunogenicity, safety and tolerability of anti-pneumococcal vaccination in systemic lupus erythematosus patients: An evidence-informed and PRISMA compliant systematic review and meta-analysis - Adawi, Mohammad; Bragazzi, Nicola Luigi; McGonagle, Dennis; Watad, Samaa; Mahroum, Naim; Damiani, Giovanni; Conic, Rosalynn; Bridgewood, Charlie; Mahagna, Hussein; Giacomelli, Luca; Eggenhöffner, Roberto; Mahamid, Mahmud; et al. (Autoimmunity reviews, 2019)
The immunological perturbations associated with systemic lupus erythematosus (SLE) put many patients at a higher risk of infections, including pneumococcal pneumonia. However, the uptake and utility of anti-pneumococcal vaccines in SLE patient is both controversial and not completely agreed upon. Indeed, several epidemiological studies of anti-pneumococcal vaccine safety and efficacy in SLE have reported short-term immunogenicity with elevated anti-pneumococcal antibody titres but inconsistent long-term findings, with some studies finding poor responses, mainly for long-term immune protection. Moreover, the safety and efficacy of the pneumococcal vaccine in SLE patients remains controversial due to the different types of anti-pneumococcal vaccines, and the heterogeneity of SLE patients. Several reviews addressing anti-pneumococcal vaccination in SLE patients exist, however, to the best of our knowledge, the present is the first systematic review and meta-analysis. To better understand the efficacy and safety of pneumococcal vaccination in SLE, a comprehensive literature search was performed identifying 18 studies, which have been included in the present systematic review and meta-analysis. All studies were designed as longitudinal investigations, 2, in particular, were of high quality, being randomized, double-blind trials (RCTs). Four studies had control groups. Total sample size included 601 participants. Vaccine immunogenicity in terms of subjects with protective antibody titers ranged from 36% to 97.6%. According to our systematic review and metanalysis, high erythrocyte sedimentation rate (ESR), older age, earlier SLE onset, high disease activity, and immunosuppressive therapy were predictors of poor immunogenicity, although belimumab was found to have no significant impact. With regard to safety, no serious adverse events were found, with up to one third of cases reporting mild/low-grade complaints. In conclusion, due to the high risk of pneumococcal infection in SLE patients and given the safety and, at least partial, effectiveness, according to our systematic review and meta-analysis, in such patients, preventive strategies mainly by immunization, are required in all age groups and, in those needing immunosuppressive therapy, immunization should be given prior the initiation of the treatment. PROSPERO registration code CRD42018103605.